Microbiota-friendly diet ameliorates hypoalbuminemia in chronic kidney disease: evidence from NHANES - Wang, Xiaoyan; Wen, Pengfei; Gao, Fang; Zhao, JinXiu; Miao, Shuchuan (Frontiers in Immunology, 2025)
Chronic kidney disease (CKD) is a global health issue, affecting approximately 10% of the population. Hypoalbuminemia, a common complication in advanced CKD, is associated with poor prognosis. This study aimed to investigate the association between a microbiota-friendly dietary scoring system (Dietary Index for Gut Microbiota, DI-GM) and serum albumin levels in patients with CKD. We utilized a cross-sectional cohort from the NHANES 2007–2018, which included 2,947 CKD patients. Multivariable logistic regression and restricted cubic spline models were applied to analyze the relationship between DI-GM scores and serum albumin. Higher DI-GM scores were significantly associated with increased serum albumin levels (β = 0.18 g/L, 95% CI: 0.07–0.28, p = 0.002). Furthermore, each 1-point increase in DI-GM score was linked to a 15% reduction in the odds of hypoalbuminemia (OR: 0.85, 95% CI: 0.74–0.97, p = 0.014). The findings suggest that a high DI-GM diet may have beneficial effects in managing hypoalbuminemia in CKD patients by modulating gut microbiota composition and reducing inflammation. This diet pattern could be a promising dietary intervention for improving clinical outcomes in CKD patients, especially those at risk for malnutrition and inflammation.